2017
DOI: 10.1364/prj.5.000431
|View full text |Cite
|
Sign up to set email alerts
|

Performance analysis of ghost imaging lidar in background light environment

Abstract: The effect of background light on the imaging quality of three typical ghost imaging (GI) lidar systems (namely narrow pulsed GI lidar, heterodyne GI lidar, and pulse-compression GI lidar via coherent detection) is investigated. By computing the signal-to-noise ratio (SNR) of fluctuation-correlation GI, our analytical results, which are backed up by numerical simulations, demonstrate that pulse-compression GI lidar via coherent detection has the strongest capacity against background light, whereas the reconstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
2

Year Published

2018
2018
2025
2025

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(21 citation statements)
references
References 19 publications
0
19
0
2
Order By: Relevance
“…Many studies have demonstrated that, in the first case, GI is more robust against disturbance from medium turbulence and medium scattering than traditional imaging techniques [34][35][36][37][38]. In the latter case, interference from optical background noise has been shown to decrease the quality of a lidar image [39]. The imaging capability of ghost imaging is reduced, or possibly even disabled, when variation in the amplitude of noise light exceeds the intensity of the thermal light.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have demonstrated that, in the first case, GI is more robust against disturbance from medium turbulence and medium scattering than traditional imaging techniques [34][35][36][37][38]. In the latter case, interference from optical background noise has been shown to decrease the quality of a lidar image [39]. The imaging capability of ghost imaging is reduced, or possibly even disabled, when variation in the amplitude of noise light exceeds the intensity of the thermal light.…”
Section: Introductionmentioning
confidence: 99%
“…optical encryption [9], [10], remote sensing [11], lidar detection [12]- [15], etc. However, the poor visibility and large measurement time in GI have hindered real applications; therefore, improvements of the image quality and imaging efficiency are required.…”
Section: Introductionmentioning
confidence: 99%
“…Another advantage of ISPI is its resistance to optical background noise. SPI and CGI can both resist turbulence and scattering medium [52][53][54] but do not have a strong capacity for resisting optical background noise [55,56]. We have experimentally verified that ISPI has excellent resistance to optical background noise.…”
Section: Discussionmentioning
confidence: 89%